Perceived organizational support (POS) across 54 nations: a cross-cultural meta-analysis of POS effects - Rockstuhl, Thomas (2022)
The authors meta-analyze relationships of perceived organizational support (POS) with attitudinal and behavioral outcomes in Western (i.e., horizontal-individualistic) and Eastern (i.e., vertical-collectivistic) cultures. The social-exchange perspective suggests that POS effects are stronger in Western cultures because employees are more likely to see the self as independent and understand their relationship with the organization in terms of reciprocity. However, the social-identity perspective suggests that POS effects are stronger in Eastern cultures because employees are more likely to see the self as interdependent and are more attuned to organizational support as an identity-related cue. Addressing these competing hypotheses, meta-analytic results from 827 independent samples (n = 332,277) across 54 countries show support for both perspectives. In the West, POS was more strongly associated with social-exchange processes than organizational-identification processes. In contrast, In the East, POS was more strongly associated with organizational-identification processes than social-exchange processes. Overall, POS was more strongly related to job attitudes and performance in the East than in the West. Cultural differences in POS effects on attitudinal outcomes were found to be increasing over time. We discuss the implications of these findings for organizational-support theory and research.